PAPARAN KONSELING TERHADAP PENGETAHUAN DONOR DARAH PADA SISWA KELAS XI SMK NEGERI 1 JEPARA - Rina Puspita (JURNAL ILMIAH EDUNOMIKA, 2021)
School age is a productive age, an asset for the future, as a channel for promoting blood donation in the community, SMK Negeri 1 Jepara has never had any outreach activities about blood donation. It is the closest school to UDD PMI Jepara Regency. The results of interviews with PMR teachers at SMK Negeri 1 Jepara are known to have reported that on average students are afraid to donate blood, are afraid of needles, do not meet the criteria for blood donation, their blood will decrease or run out, do not know the benefits of donating blood, sell their blood, are afraid of contracting disease, become sick, there are systemic diseases and so on. This study aims to determine the exposure to blood donor counseling in class XI students of SMK Negeri 1 Jepara. This type of research is an analytic survey with a cross sectional design. The research population was all students of class XI SMK Negeri 1 Jepara. The sampling technique used purposive sampling as many as 84 students. The data includes regression analysis and coefficient of determination. The regression analysis test after being given blood donation counseling showed a significant effect on blood donor knowledge in students, P Value was 0.024 < 0.05 (P Value < 0.05). The conclusion obtained is that there is counseling exposure to blood donor knowledge in class XI students of SMK Negeri 1 Jepara.